Frequency and independent risk factors of sarcopenia in type 2 diabetes - Bahar Ozdemir; Pinar Karakaya; Bulent Yaprak; Hakan Kocoglu (National Scientific Medical Center, 2019)
Background: Diabetes is a growing public health problem with the increasing obesity prevalence, and aging world population. Many comorbidities, frailty, and deteriorations in both quality of life and the health status of these patients are associated with a compound outcome of increased body mass index, aging and sarcopenia. Sarcopenia has particular importance, since it is both a cause and an outcome in these patients. Aim: The aim of this study is to evaluate the sarcopenia frequency, and to determine the independent predictors of sarcopenia in patients with type 2 diabetes. Methods: Patients between 18 to 65 years of age that followed-up at the Endocrinology Department of Istanbul Bakirkoy Dr. Sadi Konuk Education and Research Hospital with a diagnosis of type 2 diabetes mellitus were evaluated retrospectively. Results: A total of 86 patients (F/M 60/26) with a mean age of 52.9±12.4 years were included. Fifty-four patients (62.8%) had sarcopenia (70% of females and 46.2% of males; p=0.040), and albumin levels were significantly higher in those patients (p=0.037). Multivariate analyses revealed that females (OR: 3.9; p=0.020), and increased BMI (OR: 1.1 per unit increase; p=0.040), albumin (OR: 2.7 per unit increase; p=0.028) and LDL (OR: 1.02 per unit increase; p=0.016), and decreased Tg (OR: 1.01 per unit decrease; p=0.004) levels were independent determinants of sarcopenia. Conclusion: Results of this current study confirmed the previous knowledge on the subject, moreover contributes to the available evidence with reporting the increased albumin as a novel risk factor for the sarcopenia.